The effect of sediment mixing on mercury dynamics in two intertidal mudflats at Great Bay Estuary, New Hampshire, USA - Brown, Lauren E.; Chen, Celia Y.; Voytek, Mary A.; Amirbahman, Aria (Marine chemistry, 2015)
Estuarine sediments store particulate contaminants including mercury (Hg). We studied Hg sediment dynamics in two intertidal mudflats at Great Bay estuary, NH, over multiple years. Sediments at both mudflats were physically mixed down to ~10cm, as determined by 7Be measurements, albeit via different mechanisms. Portsmouth mudflat (PT) sediments were subject to bioturbation by infaunal organisms and Squamscott mudflat (SQ) sediments were subject to erosion and redeposition. The presence of higher concentrations of fresh Fe(III) hydroxide at PT suggested bioirrigation by the polychaetes (Nereis virens). At depths where infaunal bioirrigation was observed, pore-water inorganic Hg (Hgi) and methylmercury (MeHg) were lower potentially due to their interaction with Fe(III) hydroxide. Methylmercury concentrations increased immediately below this zone in some samples, suggesting that the observed increase in material flux in bioirrigated sediments may initiate from lower depths. Pore water in sediment at PT also had higher fractions of more protein-like and labile DOC than those at SQ that can lead to increased MeHg production in PT, especially at depths where Hgi is not removed from solution by Fe(III) hydroxide. Where sediment erosion and redeposition were observed at SQ, Hg species distribution was extended deeper into the sediment column. Moreover, methyl coenzyme M reductase (MCR) and mercury reductase (mer-A) genes were higher at SQ than PT suggesting differences in conditions for Hg cycling. Results showed that the near-surface region of high MeHg concentrations commonly observed in unmixed sediments does not exist in physically mixed sediments that are common in many estuarine environments. •We studied mercury cycling and transformation in two physically mixed estuarine sediments.•The oxidized iron produced by polychaetes acted to remove pore-water Hg, resulting in higher KD for Hg.•In sediments mixed by flow, MeHg distribution was extended deeper into the sediment.